2012
DOI: 10.1089/sur.2011.041
|View full text |Cite
|
Sign up to set email alerts
|

Infected Prosthetic Dialysis Arteriovenous Grafts: A Single Dialysis Center Study

Abstract: Background: The prosthetic arteriovenous grafts (AVG) being used increasingly to create hemodialysis access are prone to infections that pose potentially life-threatening infectious and bleeding complications, as well as loss of dialysis access. In this study, we identified the bacteriologic agents of infected AVGs by site swab, blood culture, and prosthesis cultures, and to evaluate the role of microbiological findings in the management of the infection. Methods: We focused on 51 patients with 53 AVGs operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…Although this technology has been useful for many years, one of its frequent failure modes in the clinic is that of bacterial colonization and infection. [1][2][3] Following implantation and hemodialysis access, it has been reported that as many as 28% of synthetic vascular grafts, 4 such as those constructed from expanded polytetrafluorethylene (ePTFE), will require revision or explant due to infection, which significantly impacts medical costs and patient morbidity. 5,6 It has been suggested that the microporous structure and synthetic composition of ePTFE grafts provide niches for bacterial accumulation 7 and interferes with the ability of host leukocytes to combat bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this technology has been useful for many years, one of its frequent failure modes in the clinic is that of bacterial colonization and infection. [1][2][3] Following implantation and hemodialysis access, it has been reported that as many as 28% of synthetic vascular grafts, 4 such as those constructed from expanded polytetrafluorethylene (ePTFE), will require revision or explant due to infection, which significantly impacts medical costs and patient morbidity. 5,6 It has been suggested that the microporous structure and synthetic composition of ePTFE grafts provide niches for bacterial accumulation 7 and interferes with the ability of host leukocytes to combat bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, bacterial infection is the second leading cause of death in hemodialysis patients with end-stage renal disease. 10 Gram-positive Staphylococcus aureus is responsible for the majority of vascular access infections 4,11 and subsequently linked to higher rates of patient mortality from serious medical complications including infective endocarditis and osteomyelitis. 12 Staphylococci have been shown to strongly adhere to the surface of implanted materials and then form a biofilm that often enables the bacterial infection to persist, despite prolonged antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study did not confirm a correlation with diabetes. Infection complications related to the AVG are well known; however, its correlation with age was not confirmed 15 .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It has been found to account for about 35% of patients losing AV grafts. 5 S. aureus is the leading cause of AV graft infection, 6 and MRSA has emerged as the most prevalent pathogen. 7 Evidence suggests that mortality associated with MRSA infection is much higher than mortality from methicillin-susceptible S. aureus infection.…”
mentioning
confidence: 99%